Tracking the impact of multiple sclerosis on employment status: the development of a questionnaire - Cores, Evangelina Valeria; Steinberg, Judith; Cuesta, Carolina; Curbelo, María Celeste; Osorio, Mabel Alicia; Bauer, Johana Julia; Politis, Daniel Gustavo (Arquivos de Neuro-Psiquiatria, 2022)
Background Multiple sclerosis (MS) has a negative effect on employment status.Objective To present the preliminary results of a special questionnaire designed to collect employment information on patients with MS.Methods The questionnaire on the impact of MS on employment status was completed by 63 patients. Fatigue, cognition, and depression were also evaluated, and 33 healthy participants were recruited as a control group.Results Regarding the patients' employment status, we found rates of 31.7% of full-time employment, 28.6% of part-time employment, 7.9% of unemployment due to MS, 4.8% of housewives, 1.6% retirement due to age, 15.9% of retirement due to disability, 7.9% of medical leave due to MS, and 1.6% of medical leave for other reasons. The rate of unemployment among the patients was significantly higher compared with that of the control group. Out of 38 working patients, 31% had been absent from work for the previous 3 months due to MS, and 50% had to make changes in their work to remain employed. Out of the 19 unemployed patients, 78% said that walking difficulties were the cause of unemployment, while 52% thought cognitive impairment was the cause.Conclusions The questionnaire provides a record of the employment status of patients with MS and describes the impact on work from their point of view.
Keywords: Surveys and Questionnaires; Unemployment; Work; Multiple Sclerosis; Disability Evaluation